Ripe for refinement: The state's role in interpretation of FET, MFN, and shareholder rights - Lise Johnson (University of Oxford, Global Economic Governance Programme (GEG), 2015)
Over recent years, many states have taken steps to refine and modernize their investment treaties. They have done this to, among other things, clarify what were often vaguely worded standards, insert provisions on procedural and jurisdictional questions, and expand the express ability of states to issue binding interpretations on certain questions. Together, these reforms can help narrow states' exposure to claims and liability under investment treaties. Those reforms, however, are typically only included in newer treaties or model agreements. States typically have legacies of existing treaties that are "old-style" and therefore are still exposed to claims, litigation, and potential damages awarded under those agreements. To mitigate that exposure, states can exercise the important powers they possess as "masters of their treaties" and use practice and agreement to help shape interpretation of treaty provisions. This note focuses on this strategy. In addition to setting out the general rules regarding state practice and agreement as a means of influencing treaty interpretation, it (1) identifies three issues in investment treaty law - FET, MFN, and shareholder rights - that may be particularly ripe for proactive efforts by states applying this interpretive strategy; and (2) sets out a series of questions that aim to facilitate interstate efforts to identify consensus on these controversial treaty provisions.
Keywords: 330; Außenwirtschaftspolitik; Internationales Investitionsrecht; Internationales Abkommen